Application of Blending Learning Based on Network Learning Space in Teaching Design of Digital Art - Wang, Jian (International Journal of Emerging Technologies in Learning (iJET), 2019)
In traditional face-to-face teaching mode, the teacher plays the leading role in the learning process, while students are in the subordinate status. Such learning mode can be easily interrupted due to the ending of classroom teaching time. To let students keep continuous learning, network learning mode based on information technology emerges. In network learning mode, students have strong learning autonomy, and can arrange learning contents and progress according to their ability and time. However, network learning mode requires students owning strong self-discipline ability to plan and arrange the learning contents and practice. A blending learning mode which can deeply integrate online learning and face-to-face teaching was established on the basis of network learning space, and applied in teaching practice of Digital Art. The results of teaching practice showed that, blending learning has significant effect on improving teaching effect of Digital Art.